Observations on the beech woodlands of the Apennines (peninsular Italy): an intricate biogeographical and syntaxonomical issue - Di Pietro, Romeo (Lazaroa, 2010)
The Apennines area is very interesting froma a biogeographical point of view, since it behaves as a natural point of contact between floristic units of different origin and provenance. Its transitional geographical position, associated to very particular bioclimatic and lithomorphological features, means it is characterised by a very complex vegetational pattern to which it is not often easy to provide an adequate syntaxonomical scheme. The Apennines beech woodlands therefore pose a syntaxonomical difficult issue. Moving southwards, the huge latitudinal extent of the Apennines range, which connects the south-western Alps and Sicily, undergoes a progressive impoverishment of the central-European floristic component of Fagion sylvaticae (still abundant in the northern Apennines) and in an increase in the endemic and Apennine-Balkan components of Geranio versicoloris-Fagion (southern Apennines)as it traverses the Aremonio-Fagion Apennine-Dinaric window (central Apennines). This general scheme, which is especially valid for basic substrates, partially excludes the acidophitic beech woodlands which have tradionally been included in other kinds of syntaxa. However the classic ecological classification of European beech woodlands, based on soil pH, which serves to separate basiphilous beech woodlands (Fagion, Fagetalia) and acidophilous beech woodlands (Luzulo-Fagion, Quercetalia robori-petraeae) at the rank of alliance and order, would appear not to be applicable to the Apennines. In this case, moving from the northern Apennines to the southern Apennines, the ecological criterion loses progressively and is replaced by others suchas the biogeographical or the altitudinal ones.